A comprehensive review on carotenoids in foods and feeds: status quo, applications, patents, and research needs - Meléndez-Martínez, Antonio J.; Mandić, Anamarija I.; Bantis, Filippos; Böhm, Volker; Borge, Grethe Iren A.; Brnčić, Mladen; Bysted, Anette; Cano, M. Pilar; Dias, M. Graça; Elgersma, Anjo; Fikselová, Martina; García-Alonso, Javier; et al. (Critical reviews in food science and nutrition, 2022)
Carotenoids are isoprenoids widely distributed in foods that have been always part of the diet of humans. Unlike the other so-called food bioactives, some carotenoids can be converted into retinoids exhibiting vitamin A activity, which is essential for humans. Furthermore, they are much more versatile as they are relevant in foods not only as sources of vitamin A, but also as natural pigments, antioxidants, and health-promoting compounds. Lately, they are also attracting interest in the context of nutricosmetics, as they have been shown to provide cosmetic benefits when ingested in appropriate amounts. In this work, resulting from the collaborative work of participants of the COST Action European network to advance carotenoid research and applications in agro-food and health (EUROCAROTEN, www.eurocaroten.eu , https://www.cost.eu/actions/CA15136/#tabs|Name:overview ) research on carotenoids in foods and feeds is thoroughly reviewed covering aspects such as analysis, carotenoid food sources, carotenoid databases, effect of processing and storage conditions, new trends in carotenoid extraction, daily intakes, use as human, and feed additives are addressed. Furthermore, classical and recent patents regarding the obtaining and formulation of carotenoids for several purposes are pinpointed and briefly discussed. Lastly, emerging research lines as well as research needs are highlighted.